Preparation method and application of BiVO4 / CuFe2O4 composite photo-anode

By preparing BiVO4/CuFe2O4 composite photoanode, CuFe2O4 and BiVO4 form a heterostructure, the problems of serious charge recombination and slow water oxidation kinetics are solved, and efficient photoelectrocatalytic water decomposition effect is achieved.

CN119913559AActive Publication Date: 2025-05-02TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510096535.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-12
Publication Date
2025-05-02
Estimated Expiration
2045-01-12

AI Technical Summary

Technical Problem

Due to the poor charge transport characteristics and short hole diffusion length of BiVO4 photoelectrodes, severe charge recombination and slow water oxidation kinetics, limiting its practical application potential.

Method used

Using the preparation method of BiVO4/CuFe2O4 composite photoanode, the FTO conductive glass is used as the working electrode, and the aqueous solution containing bismuth nitrate and potassium iodide is mixed with the ethanol solution of parabenzoquinone as the electrolyte, and BiOI is deposited at a certain potential. Then the dimethyl sulfoxide solution of acetylacetonate vanadium acetylacetonate is dripped and calcined to form a BiVO4 electrode. Then the CuFe2O4 powder is dissolved in anhydrous ethanol and dripped on the BiVO4 electrode, and the BiVO4/CuFe2O4 composite photoanode is obtained after heat treatment.

Benefits of technology

CuFe2O4 and BiVO4 form a heterostructure, which significantly accelerates the transfer and separation of charge, inhibits hole recombination, improves photocurrent density and electrode stability, and significantly improves the hydrooxidation kinetics of BiVO4 photoanode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913559A_ABST
    Figure CN119913559A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a BiVO4 / CuFe2O4 composite photo-anode for photoelectrocatalytic water decomposition. According to the invention, BiVO4 is used as a substrate, and the BiVO4 / CuFe2O4 composite photo-anode is prepared by using a dispensing and calcining method. The supported spinel type CuFe2O4 accelerates separation of current carriers, inhibits recombination of holes and improves water oxidation kinetics, so that the composite photoanode has excellent photoelectrochemical water decomposition capability and good stability, and under the illumination condition, the photoelectrocatalytic performance of the BiVO4 / CuFe2O4 composite photoanode is far higher than that of a BiVO4 photoelectrode. Meanwhile, the composite photo-anode is low in raw material and synthesis cost, and the synthesis method is simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrocatalysis, and specifically relates to a method for preparing a BiVO4 / CuFe2O4 composite photoelectrode and its application in photoelectrocatalytic decomposition of water. Background Art

[0002] Photoelectrocatalytic water splitting to produce hydrogen is a clean energy technology. Its basic principle is to use light energy to activate the catalyst and promote the decomposition of water molecules under the action of an external circuit to produce hydrogen and oxygen. This technology has the potential to convert solar energy into chemical energy and is regarded as a sustainable future energy solution. Therefore, the development of efficient photoelectrocatalytic water splitting technology is of great significance for reducing dependence on fossil fuels and reducing greenhouse gas emissions. Among the many photoanode materials, bismuth vanadate (BiVO4) has attracted widespread attention due to its high theoretical photocurrent density and conversion efficiency. However, due to the poor charge transport properties of BiVO4 photoelectrode (carrier mobility is 0.044cm 2 V -1 s -1 ) and short hole diffusion length (<70 nm), resulting in severe charge recombination and slow water oxidation kinetics, greatly limiting its potential for practical applications.

[0003] Heteroatom doping, structural construction, crystal surface engineering, heterostructure construction, defect engineering, and loading of oxygen evolution co-catalysts (OECs) are considered to be effective strategies to improve the water oxidation activity of BiVO4 photoelectrodes PEC. It should be mentioned that the oxygen evolution reaction (OER) is a complex four-electron transfer process, and modifying the BiVO4 surface with appropriate OECs is of great significance for suppressing surface charge recombination. However, modifying the BiVO4 surface with some highly active OECs does not always achieve high photoelectrocatalytic performance, because the driving force at the OEC / BiVO4 interface is small and all photogenerated holes cannot be extracted from BiVO4 in time for OER. Therefore, it is urgent to develop an efficient photoelectrocatalytic material that suppresses charge recombination at the OEC / BiVO4 interface for photoelectrochemical water splitting. Summary of the invention

[0004] In view of the problems of severe charge recombination and slow water oxidation kinetics of BiVO4 photoelectrode, the present invention provides a method for preparing a BiVO4 / CuFe2O4 composite photoanode for efficient photoelectrocatalytic water decomposition.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing a BiVO4 / CuFe2O4 composite photoanode, the preparation steps comprising:

[0007] S1: A three-electrode system was constructed using FTO conductive glass as the working electrode, Ag / AgCl as the reference electrode, and platinum as the counter electrode. An aqueous solution containing bismuth nitrate and potassium iodide was mixed with an ethanol solution containing p-benzoquinone as the electrolyte, and the electrode was deposited at a certain potential. The resulting electrode was recorded as BiOI.

[0008] S2: A dimethyl sulfoxide solution containing vanadium acetylacetonate is dripped onto the BiOI electrode, which is then calcined in a muffle furnace. After cooling to room temperature, the electrode is immersed in a NaOH solution for 20 to 30 minutes. The product is taken out, washed and dried, and is recorded as BiVO4.

[0009] S3: Heat the aqueous solution containing copper nitrate, iron nitrate and citric acid to 50-100°C in a drying oven and keep it for 10-12 hours. After cooling to room temperature, grind the obtained substance into powder, and then calcine it in a muffle furnace. The powder obtained after taking out and grinding is recorded as CuFe2O4;

[0010] S4: The CuFe2O4 powder is dissolved in anhydrous ethanol, and the powder is dripped on the BiVO4 electrode, and then placed in a muffle furnace for calcination. The electrode obtained after taking out is recorded as BiVO4 / CuFe2O4.

[0011] Furthermore, the concentration of bismuth nitrate in the S1 aqueous solution is 0.04-0.06 mol / L, the concentration of potassium iodide is 0.04-0.06 mol / L, the concentration of p-benzoquinone solution is 0.2-0.3 mol / L, the volume ratio of the aqueous solution to the ethanol solution is 5:2, the deposition potential is -0.1±0.05V vs.Ag / AgCl, and the deposition time is 400-500s.

[0012] Preferably, the concentration of bismuth nitrate is 0.05 mol / L, the concentration of potassium iodide is 0.05 mol / L, the concentration of p-benzoquinone solution is 0.23 mol / L, the deposition potential is -0.1 V vs. Ag / AgCl, and the deposition time is 400 s.

[0013] Furthermore, the concentration of vanadium acetylacetonate in S2 is 0.1-0.3 mol / L, the calcination temperature in the muffle furnace is 400-500° C., the heating rate is 1-3° C. / min, and the holding time is 0.5-1.5 h.

[0014] Preferably, the concentration of vanadyl acetylacetonate is 0.2 mol / L, the calcination temperature in the muffle furnace is 450° C., the heating rate is 2° C. / min, and the holding time is 1 h.

[0015] Furthermore, copper nitrate, ferric nitrate and citric acid in S3 are mixed in a molar ratio of 1:2:3, the calcination temperature in the muffle furnace is 400-500°C, the heating rate is 3-5°C / min, and the holding time is 4-6h.

[0016] Preferably, the calcination temperature in the muffle furnace is 500° C., the heating rate is 4° C. / min, and the holding time is 5 h.

[0017] Furthermore, the concentration of CuFe2O4 solution in S4 is 0.05-0.15 mol / L, the calcination temperature in the muffle furnace is 150-200°C, the heating rate is 5-10°C / min, and the holding time is 0.5-1.5h.

[0018] Preferably, the concentration of the CuFe2O4 solution is 0.10 mol / L, and the calcination temperature in the muffle furnace is 180°C.

[0019] Based on the same inventive concept, the present invention also provides a preparation method and application of a BiVO4 / CuFe2O4 composite photoanode.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention combines CuFe2O4 powder with BiVO4 electrode by drip coating and heat treatment. The synthesis method is simple and the raw material sources are wide.

[0022] (2) The CuFe2O4 nanoparticles prepared by the present invention can form a heterostructure with BiVO4. Under sunlight, both CuFe2O4 and BiVO4 will generate electron-hole pairs. Since CuFe2O4 and BiVO4 form a heterostructure, photogenerated electrons can easily move from the conduction band of CuFe2O4 to the conduction band of BiVO4 and be collected on the FTO substrate and transmitted to the photocathode through an external circuit; while photogenerated holes transfer from the valence band of BiVO4 to the valence band of CuFe2O4 and participate in the water oxidation reaction. This can not only accelerate the transfer and separation of charges, but also inhibit the recombination of holes, so that the BiVO4 / CuFe2O4 composite electrode exhibits a higher photocurrent density.

[0023] (3) The CuFe2O4 nanoparticles loaded on the BiVO4 surface have excellent chemical stability, which can effectively inhibit photocorrosion and greatly improve the electrode stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction patterns of BiVO4 and BiVO4 / CuFe2O4 composite electrodes prepared in Example 1.

[0025] Figure 2 This is a scanning electron microscope image of the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0026] Figure 3This is a transmission electron microscope image of the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0027] Figure 4 This is the full scan spectrum of the X-ray photoelectron spectrum of the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0028] Figure 5 The linear sweep voltammetry curves of the BiVO4 electrode and the BiVO4 / CuFe2O4 composite electrode prepared in Example 1 under light.

[0029] Figure 6 2 are charge separation efficiency curves of the BiVO4 electrode and the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0030] Figure 7 The electron lifetime curves of the BiVO4 electrode and the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0031] Figure 8 Tafel slope curves of the BiVO4 electrode and the BiVO4 / CuFe2O4 composite electrode prepared in Example 1.

[0032] Fig. 9 The stability curves of the BiVO4 electrode and the BiVO4 / CuFe2O4 composite electrode prepared in Example 1 under light irradiation.

[0033] Fig.10 The linear sweep voltammetry curve of the BiVO4 / CuFe2O4 composite electrode prepared in Example 2 under light.

[0034] Fig.11 The linear sweep voltammetry curve of the BiVO4 / CuFe2O4 composite electrode prepared in Example 3 under light. DETAILED DESCRIPTION

[0035] The technical scheme of the present invention is further described below by specific embodiments and accompanying drawings. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0036] Example 1

[0037] The preparation method of the BiVO4 / CuFe2O4 composite electrode of this embodiment 1 comprises the following steps:

[0038] (1) A three-electrode system was formed using FTO conductive glass as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl (saturated KCl solution) as the reference electrode. A 50 mL aqueous solution containing 0.5 g bismuth nitrate and 3 g potassium iodide and having a pH of about 1.7 was mixed and stirred with a 0.23 mol / L p-benzoquinone solution as an electrolyte, and a potential of -0.1 V vs. Ag / AgCl was used for deposition for 400 s to obtain a BiOI electrode.

[0039] (2) 60 μL of 3 mL of dimethyl sulfoxide solution containing 0.16 g of acetylacetonato vanadyl was dropped onto the surface of the BiOI electrode obtained in (1) to make the acetylacetonato vanadyl solution evenly cover the surface of the BiOI material, and then put it into a muffle furnace, heat it to 450°C at a rate of 2°C / min, keep it warm for 1 hour, and naturally cool it to room temperature; the taken out BiVO4 electrode was placed in a 1 mol / L NaOH aqueous solution for 25 minutes to remove the residual V2O5 on the surface of the BiVO4 electrode, and then it was repeatedly washed with deionized water to obtain a BiVO4 electrode;

[0040] (3) copper nitrate, ferric nitrate and citric acid were dissolved in 100 mL of deionized water in a molar ratio of 1:2:3, placed in a drying oven at 100°C for 10 h, then taken out and fully ground, and then the powder was placed in a muffle furnace and heated to 500°C for 5 h to obtain CuFe2O4 powder;

[0041] (4) 60 μL of 0.10 mol / L CuFe2O4 solution was dropped onto the BiVO4 electrode, which was then placed in a drying oven and heated to 180°C for 1 h to obtain a BiVO4 / CuFe2O4 composite electrode;

[0042] (5) Test the photoelectrocatalytic performance of the above materials.

[0043] Example 2

[0044] Referring to the method of Example 1, the concentration of CuFe2O4 solution was changed to 0.3 mol / L and then dropped onto the BiVO4 electrode, which was then placed in a drying oven and heated to 180°C for 2 hours. Other steps and parameters were the same as those of Example 1.

[0045] Example 3

[0046] Referring to the method of Example 1, the concentration of CuFe2O4 solution was changed to 0.05 mol / L and then dropped onto the BiVO4 electrode, which was then placed in a drying oven and heated to 180°C for 2 hours. Other steps and parameters were the same as those of Example 1.

[0047] Characterization and detection

[0048] Figure 1This is the X-ray diffraction spectrum of the BiVO4 / CuFe2O4 photoanode prepared in Example 1. It can be seen that the main diffraction peaks in the spectrum are consistent with the characteristic peaks of BiVO4 (JCPDS No. 14-0688) and SnO2 (FTO substrate) (JCPDS No. 46-1088); the BiVO4 / CuFe2O4 photoelectrode prepared in Example 1 was characterized by scanning electron microscopy, and the results are as follows Figure 2 As shown, after loading CuFe2O4 nanoparticles, the BiVO4 surface is covered with accumulated tiny particles. Figure 3 This is a transmission electron microscope image of the BiVO4 / CuFe2O4 composite photoanode. The crystal lattice can be clearly seen. The crystal planes with lattice spacing of 0.181nm and 0.21nm belong to the (202) crystal plane of BiVO4 and the (400) crystal plane of CuFe2O4, respectively. Figure 4 The full scan X-ray photoelectron spectroscopy spectrum proves that CuFe2O4 nanoparticles are successfully loaded on BiVO4.

[0049] In the photoelectrocatalytic water splitting test system, photocurrent density is a test method to measure the semiconductor's absorption and conversion efficiency of light energy. The photoelectrocatalytic water splitting test performance is measured by an electrochemical analyzer (CHI660E) with a standard three-electrode system, in which the platinum sheet is used as the counter electrode, the photoelectrode to be tested is used as the working electrode, and the Ag / AgCl electrode is used as the reference electrode. The light source is simulated sunlight AM 1.5G (100mW cm -2 ), the electrolyte was 0.5 M potassium borate (KBi) solution (pH = 9.5), and the optical power was calibrated to 100 mW cm by a power meter. -2 The potential range of the linear scanning curve (LSV) for photoelectrocatalytic performance test was 0 V to 1.5 V vs. RHE, and the scanning rate was 20 mV s -1 .

[0050] Figure 5 The linear voltammetric curves of BiVO4 and BiVO4 / CuFe2O4 photoanode prepared in Example 1. Compared with the BiVO4 photoelectrode, the photocurrent density of the BiVO4 / CuFe2O4 photoelectrode is 2.77 mA cm at 1.23 V vs. RHE. -2 , which is twice that of the BiVO4 electrode, indicating that the PEC performance is greatly improved after the combination of CuFe2O4 nanoparticles. In order to illustrate that the CuFe2O4 nanoparticles loaded on the BiVO4 photoanode can improve the separation of carriers and inhibit the recombination of carriers, the charge separation efficiency and electron life test of the BiVO4 electrode and BiVO4 / CuFe2O4 electrode obtained in Example 1 were further tested. Figure 6As shown in Figure 2, the charge separation efficiency of the BiVO4 / CuFe2O4 electrode is 75.8%, which is much higher than the 66.5% of the BiVO4 electrode, proving that the loading of CuFe2O4 nanoparticles accelerates the charge separation; Figure 7 The electron lifetime test shows that the electron lifetime of the BiVO4 / CuFe2O4 electrode is 3.5s, which is longer than the 2.4s lifetime of the BiVO4 electrode, proving that the loading of CuFe2O4 nanoparticles can inhibit the recombination of carriers and prolong the lifetime of photogenerated carriers.

[0051] In order to prove that CuFe2O4 nanoparticles can improve the water oxidation kinetics of BiVO4 photoelectrode, Tafel slope test was performed on BiVO4 and BiVO4 / CuFe2O4 electrodes. The test can directly reflect the catalytic activity by the size of the slope. The smaller the slope, the higher the catalytic activity and the better the water oxidation kinetics. Figure 8 As shown, the slope of the BiVO4 photoelectrode is 143mVdec -1 , while the slope of BiVO4 / CuFe2O4 photoelectrode is only 77mV dec -1 , demonstrating that the loading of CuFe2O4 nanoparticles can significantly improve the water oxidation kinetics of BiVO4 photoanode.

[0052] Fig. 9 This is a stability test chart of the BiVO4 and BiVO4 / CuFe2O4 photoelectrodes obtained in Example 1. The two photoelectrodes were tested for 8 hours under light conditions. The results showed that due to the reconstruction phenomenon, the PEC performance of the BiVO4 / CuFe2O4 photoelectrode increased instead of decreased, and the amplitude was relatively large, indicating that the BiVO4 / CuFe2O4 photoelectrode has good stability.

[0053] Fig.10 and Fig.11 The LSV of the 0.3 mol / L BiVO4 / CuFe2O4 photoelectrode and the 0.05 mol / L BiVO4 / CuFe2O4 photoelectrode obtained in Example 2 and Example 3. It can be seen from the figure that the current density of the 0.3 mol / L photoanode can reach 1.78 mA cm at a potential of 1.23 V vs. RHE. -2 The current density of the 0.05 mol / L photoanode at 1.23 V vs. RHE is 1.56 mA cm -2 Compared with BiVO4 photoanode, they have different degrees of improvement, so this invention can significantly improve the PEC performance of photoanode.

[0054] The specific embodiments described herein are merely examples of the spirit of the present invention and do not limit the scope of protection of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but they will not deviate from the spirit of the present invention or exceed the scope defined by the attached claims.

Claims

1. A method for preparing a BiVO4 / CuFe2O4 composite photoanode, characterized in that: The preparation steps include: S1: A three-electrode system was constructed using FTO conductive glass as the working electrode, Ag / AgCl as the reference electrode, and platinum as the counter electrode. An aqueous solution containing bismuth nitrate and potassium iodide was mixed with an ethanol solution containing p-benzoquinone as the electrolyte, and the electrode was deposited at a certain potential. The resulting electrode was recorded as BiOI. S2: A dimethyl sulfoxide solution containing vanadium acetylacetonate is dripped onto the BiOI electrode, which is then calcined in a muffle furnace. After cooling to room temperature, the electrode is immersed in a NaOH solution for 20 to 30 minutes. The product is taken out, washed and dried, and is recorded as BiVO4. S3: Heat the aqueous solution containing copper nitrate, iron nitrate and citric acid to 50-100°C in a drying oven and keep it for 10-12 hours. After cooling to room temperature, grind the obtained substance into powder, and then calcine it in a muffle furnace. The powder obtained after taking out and grinding is recorded as CuFe2O4; S4: The CuFe2O4 powder is dissolved in anhydrous ethanol, and the powder is dripped on the BiVO4 electrode, and then placed in a muffle furnace for calcination. The electrode obtained after taking out is recorded as BiVO4 / CuFe2O4.

2. The method according to claim 1, characterized in that The concentration of bismuth nitrate in the S1 aqueous solution is 0.04-0.06 mol / L, the concentration of potassium iodide is 0.04-0.06 mol / L, the concentration of p-benzoquinone solution is 0.2-0.3 mol / L, the volume ratio of the aqueous solution to the ethanol solution is 5:2, the deposition potential is -0.1±0.05V vs.Ag / AgCl, and the deposition time is 400-500s.

3. The method according to claim 1, characterized in that The concentration of vanadium acetylacetonate in S2 is 0.1-0.3 mol / L, the calcination temperature in the muffle furnace is 400-500°C, the heating rate is 1-3°C / min, and the holding time is 0.5-1.5h.

4. The method according to claim 1, characterized in that In S3, copper nitrate, ferric nitrate and citric acid are mixed in a molar ratio of 1:2:3, and the calcination temperature in the muffle furnace is 400-500°C, the heating rate is 3-5°C / min, and the insulation time is 4-6h.

5. The method according to claim 1, characterized in that The concentration of CuFe2O4 solution in S4 is 0.05-0.15 mol / L, the calcination temperature in the muffle furnace is 150-200°C, the heating rate is 5-10°C / min, and the holding time is 0.5-1.5h.

6. A BiVO4 / CuFe2O4 composite photoanode, characterized in that: The BiVO4 / CuFe2O4 composite photoanode is prepared by the method described in any one of claims 1-5.

7. Use of a BiVO4 / CuFe2O4 composite photoanode as described in claim 6 in photoelectrocatalytic water decomposition.

Citation Information

Patent Citations

  • Nanometer composite film material and application thereof

    CN112795926A

  • Preparation method and application of iron oxide / ferrite composite membrane

    CN114182279A

  • Preparation method of Co3O4 / WO3 / BiVO4 photo-anode

    CN114318396A

  • Preparation method of 3D printing CuFe2O4 electrode

    CN116676616A

  • Spinel type high-entropy oxide photoelectric catalytic material and application

    CN118932373A